Turnover of Plasma Esterified Cholesterol in Normocholesterolemic and Hypercholesterolemic Subjects and Its Relation to Body Build - Nestel, P. J. (1967)
The turnover rate of plasma total esterified cholesterol was measured after the intravenous injection of tritiated mevalonic acid in 16 men with coronary heart disease. Four subjects were normocholesterolemic and 12 were hypercholesterolemic; among the latter, 3 suffered from familial hypercholesterolemia and 6 were overweight. The turnover rate of plasma esterified cholesterol was highest among the overweight hypercholesterolemic subjects and least among the subjects with familial hypercholesterolemia. Hypercholesterolemic subjects of normal weight had turnover rates similar to those found in normocholesterolemic men. Significant correlations were found between body surface or body weight and the turnover rate of plasma esterified cholesterol. We conclude that the factors which determine the development of hypercholesterolemia are not identical in all hypercholesterolemic subjects and that when hypercholesterolemia is associated with overweight there is an increased formation of at least plasma esterified cholesterol.